Improving the Mechanical Properties of GlassFibre-Reinforced Laser-Sintered Parts Based on Degree of Crystallinity and Porosity Content Using a Warm Isostatic Pressing (WIP) Process - Hellen De Coninck; Jae Won Choi; Jeroen Soete; Sebastian Meyers; Brecht Van Hooreweder (Journal of Manufacturing and Materials Processing, 2024)
Additively manufactured fibre-reinforced polymers are gaining traction. After the development and optimisation of a novel fibre-deposition system in a laser sintering (LS) setup, polyamide 12 specimens were produced with and without glass fibres. In this study, the relation between the crystallinity, porosity, and mechanical properties of LS specimens with and without fibres is investigated. After testing as-built LS specimens, a detrimental effect of the fibres on the specimens’ performance was observed with a decrease in UTS of 6%. The degree of crystallinity remained the same; however, a porosity content of 2.6% was observed in specimens with fibres. These pores can have a negative influence on the bonding between the fibres and the matrix. To investigate the influence of the pores, warm isostatic pressing (WIP) was performed on LS specimens with and without fibres. The WIP process shows a positive influence on the specimens without fibres, resulting in an increase in UTS of 8.5%. The influence of the WIP process on specimens with fibres, however, is much less pronounced, with an increase in UTS of only 2%. Neither the crystallinity nor the porosity are the cause of the less-than-expected increase in UTS in LS specimens with fibres. A number of hypotheses and mitigation strategies are provided.